INVESTASI: ANALISIS DAN RELEVANSINYA DENGAN EKONOMI ISLAM - Nuril Hidayati, Amalia (MALIA (TERAKREDITASI), 2017)
Investment is a sacrifice now to benefit future. Investment opportunities need to be improved so that economic development can run smoothly, so as to realize the welfare for the wider community. Islam teaches its people to seek a better life, both in the world and in the hereafter. Investing in economic activities must be in accordance with Islamic corridors. For the Muslim investor, the economic aspect is not the only aspect to be considered, but there are other aspects to note: the spiritual moral aspect. This spiritual moral dimension is indispensable for filtering out forbidden economic activities in Islamic investment. Islam strongly advocates investment, but not all areas of business are allowed to invest. There are rules in Islam that impose restrictions on which activities are lawful and unlawful to do. It aims to control people from activities that harm society.